Inclusion Evolution and Calcium Treatment Optimization of 9Ni Steel - Chen Dengguo, Lv Jiping, Wan Yong, Dong Fujun, Cao Ruihong, Sun Lefei (Teshugang)
By means of industrial test and Aspex automatic inclusion analysis techonogy， the evolution law of ［T.O］， ［N］ content， microinclusions quantity， size and type of 9Ni steel in LF→RH→CC steelmaking process were systematically studied. The formation mechanism of calcium-aluminate and CaS inclusions under calcium treatment conditions was investigated by Factsage software. The results show that the content of ［T.O］ and ［N］ in 9Ni steel increases simultaneously in the process interval from LF first power supply→LF second power supply and RH soft blowing argon gas for 20 min→rolling， indicating that there is secondary oxidation in the molten steel in these two process intervals. The inclusions in 9Ni steel are mainly CaO-Al2O3-MgO and CaO-Al2O3-CaS complex inclusions， and the size is mainly between 2 μm-5 μm. When the calcium line is reduced from 200 m to 100 m， the density of 2 μm-5 μm inclusions in 9Ni steel rolled material is significantly reduced， and basically no inclusions containing CaS components are found， and the grades of DT and DS inclusions are reduced from 1.0 and 1.5 grades to 0.5 and 0.5 grades， respectively. The Aspex statistical results of the density， size and average composition of composite inclusions in 9Ni steel rolled sheets with 200 m and 100 m calcium line are in good agreement with the inclusion rating results and Factsage calculation results.